DEVELOPMENT OF SCENARIO CONDITIONS AS KEY STAGE OF PREPARATION OF STRATEGY OF REGION - O. I. Karasev; V. L. Pulyaevskaya; О. И. Карасев; В. Л. Пуляевская (Novosibirsk State University of Economics and Management, 2017)
The article considers scenario conditions of the most probable external and internal conditions of development of economy of the Sakha (Yakutia) Republic. The trends of the development of the world economy, dynamics of goods market and development prospects for the region economy are appraised. The medium-term forecast of the main macroeconomic indicators of the Sakha (Yakutia) Republic is presented. В данной статье рассматриваются сценарные условия наиболее вероятных внешних и внутренних условий развития экономики Республики Саха (Якутия). Дается оценка тенденций развития мировой экономики, динамики товарных рынков и перспективы развития экономики региона. Представлен прогноз основных макроэкономических показателей Республики Саха (Якутия) на среднесрочный период.